Assessment of cattle genetic introgression into domestic yak populations using mitochondrial and microsatellite DNA markers - Qi, X.B.; Wang, G.; Rege, J.E.O.; Hanotte, Olivier H.; Han Jianlin (Wiley, 2010)
Hybridization between yak Poephagus grunniens and taurine Bos taurus or indicine B. indicus cattle has been widely practiced throughout the yak geographical range, and gene flow is expected to have occurred between these species. To assess the impact of cattle admixture on domestic yak, we examined 1076 domestic yak from 29 populations collected in China, Bhutan, Nepal, India, Pakistan, Kyrgyzstan, Mongolia and Russia using mitochondrial DNA and 17 autosomal microsatellite loci. A cattle diagnostic marker-based analysis reveals cattle-specific mtDNA and/or autosomal microsatellite allele introgression in 127 yak individuals from 22 populations. The mean level of cattle admixture across the populations, calculated using allelic information at 17 autosomal microsatellite loci, remains relatively low (mYcattle = 2.66 ± 0.53% and Qcattle = 0.69 ± 2.58%), although it varies a lot across populations as well as among individuals within population. Although the level of cattle admixture shows a clear geographical structure, with higher levels of admixture in the Qinghai-Tibetan Plateau and Mongolian and Russian regions, and lower levels in the Himalayan and Pamir Plateau region, our results indicate that the level of cattle admixture is not significantly correlated with the altitude across geographical regions as well as within geographical region. Although yak-cattle hybridization is primarily driven to produce F1 hybrids, our results show that the subsequent gene flow between yak and cattle took place and has affected contemporary genetic make-up of domestic yak. To protect yak genetic integrity, hybridization between yak and cattle should be tightly controlled.